Reliability of primary caregivers reports on lifestyle behaviours of European pre‐school children: the ToyBox‐study. (August 2014) - González‐Gil, E. M.; Mouratidou, T.; Cardon, G.; Androutsos, O.; De Bourdeaudhuij, I.; Góźdź, M.; Usheva, N.; Birnbaum, J.; Manios, Y.; Moreno, L. A.
Summary: Reliable assessments of health‐related behaviours are necessary for accurate evaluation on the efficiency of public health interventions. The aim of the current study was to examine the reliability of a self‐administered primary caregivers questionnaire (PCQ) used in the ToyBox‐intervention. The questionnaire consisted of six sections addressing sociodemographic and perinatal factors, water and beverages consumption, physical activity, snacking and sedentary behaviours. Parents/caregivers from six countries (Belgium, Bulgaria, Germany, Greece, Poland and Spain) were asked to complete the questionnaire twice within a 2‐week interval. A total of 93 questionnaires were collected. Test–retest reliability was assessed using intra‐class correlation coefficient (ICC). Reliability of the six questionnaire sections was assessed. A stronger agreement was observed in the questions addressing sociodemographic and perinatal factors as opposed to questions addressing behaviours. Findings showed that 92% of the ToyBox PCQ had a moderate‐to‐excellent test–retest reliability (defined as ICC values from 0.41 to 1) and less than 8% poor test–retest reliability (ICC < 0.40). Out of the total ICC values, 67% showed good‐to‐excellent reliability (ICC from 0.61 to 1). We conclude that the PCQ is a reliable tool to assess sociodemographic characteristics, perinatal factors and lifestyle behaviours of pre‐school children and their families participating in the ToyBox‐intervention.